Ideológica y realidad material. El problema de la imaginación - González, Sebastián (2012)
“Ideology and Material Reality. The Problem of Imagination”. Are there no more options of freedom than those determined not only by the real conditions under which each one of us live, but by the scheme of functions which force us sometimes to make/feel and sometimes only let us make/feel according to a certain number of action and passion possibilities? With this question in mind, we test the hegemony and antagonisms model (Laclau and Mouffe), more with the aim of “problematizing” the theoretical alternatives whose treatment of freedom and of the role of people and groups does not emerge from transcendental considerations on the subject and her connatural rights; than with the aim of finding an answer for the determinations proposal. In this paper we propose a problematic approach to the issue of knowing whether we can or cannot give ourselves a political organization which gathers the effects of the State’s repression devices, which ignores the obscure conception of ideology as a false interpretation or as a reality deforming illusion and which does not base its considerations on the concept of subject on the already far too well known postulates of freedom, rationality, legitimate adscription to the law, dialogue and consent. Our hypothesis is that in so far as every agreement entails the at least partial stabilization of differences without implying the dissolution of antagonisms, the possibility for the complex and incomplete articulation of the involved agents arises. Consensus is therefore arrived at without exclusion. Consensus is the undecidable issue of keeping open the political link for the questioning of agents according to their demands, needs, perspectives, interests, etc. Finally, we claim that any political project with aspirations to change has a possibility in the violence of imagination.